Governing borders and security the politics of connectivity and dispersal - Kinnvall, Catarina; Svensson, Ted (Prio new security studies, 2015)
This book explores and maps the relationship between borders, security and global governance. Theoretically, the book seeks to establish to what degree, and in what ways, traditional notions of borders, security and (global) governance are being eroded, undermined and contested in the context of a globalizing world. Borders are increasingly being re-conceptualized to account for connectivity as well as divisions at the same time as focus is shifting from permanence to permeability. The ambivalence ascribed to bordering processes is at heart a security concern; borders are not only entwined with state formation but also attempts at governing securities, identities and histories. Proceeding from a critical rendering of statist conceptualizations of borders, security and governance, the book not only emphasizes the politics of borders, mobility and re-locations, but also provides a shared groundwork for interrogating the spatial conditions for bordering and border work as manifestations of a continuously deferred becoming rather than being. A principal contribution of the volume is its scrutiny of how borders are enacted and perceived in and through the everyday, and of how such production and construal can make sense as acts of resistance to various forms of governing. Such a focus reveals the necessity of investigating how governing from a distance affects the possibilities and tendencies to securitize as well as desecuritize, within as well as beyond elite settings. This book will be of much interest to students of border studies, human geography, governmentality, global governance and IR/critical security studies.